Concomitant drugs-loaded microcapsules of roxithromycin and theophylline with pH-sensitive controlled-releasing properties. Issue 11 (23rd July 2020) - Zhou, You; Qiu, Bining; Yin, Xueqiong; Liu, Haifang; Zhu, Li
Abstract: Cough variant asthma (CVA) is well-known as a subtype of asthma that is characterized by a chronic cough. Roxithromycin (ROX) and theophylline (TH) have a synergistic effect on CVA. In this study, concomitant drugs-loaded microcapsules (CDM) of ROX and TH were prepared by spray drying with amphiphilic methylcellulose (MC) and sodium Alginate (Alg) as the wall materials. The preparation conditions and wall materials components had been optimized and MC/Alg/MC had the highest encapsulation efficiency. With MC/Alg/MC as the wall material, microcapsules of concomitant drugs had higher drug loading than those of the single drug. CDM expressed obvious pH-sensitive controlled-release behavior. After 12 h releasing, the cumulative release of ROX and TH at pH 1.5 was 21.07% and 22.31%, 73.14% and 97.52% at pH 7.4, respectively. The antibacterial efficacy of pure drugs and CDM further proved that controlled-release was achieved in CDM. Cytotoxicity test on neutrophils also confirmed that CDM were less toxic to cells than the pure drugs. GRAPHICAL ABSTRACT: